Gallstone Disease and the Risk of Cardiovascular Disease - Fairfield, Cameron J. (Sci Rep, 2019)
Gallstone disease (GD) is one of the most common presentations to surgical units worldwide and shares several risk factors with cardiovascular disease (CVD). CVD remains the most common cause of death worldwide and results in considerable economic burden. Recent observational studies have demonstrated an association between GD and CVD with some studies demonstrating a stronger association with cholecystectomy. We present the findings of a meta-analysis assessing the relationship between GD and CVD. A total of fourteen cohort studies with over 1.2 million participants were included. The pooled hazard ratio (HR, 95% confidence interval [CI]) for association with GD from a random-effects model is 1.23 (95%CI: 1.16–1.30) for fatal and non-fatal CVD events. The association was present in females and males. Three studies report the relationship between cholecystectomy and CVD with a pooled HR of 1.41 (95%CI: 1.21–1.64) which compares to a HR of 1.30 (95%CI: 1.07–1.58) when cholecystectomy is excluded although confounding may influence this result. Our meta-analysis demonstrates a significant relationship between GD and CVD events which is present in both sexes. Further research is needed to assess the influence of cholecystectomy on this association.